Different mutations in the MMUT gene are associated with the effect of vitamin B12 in a cohort of 266 Chinese patients with mut‐type methylmalonic acidemia: A retrospective study. Issue 11 (20th October 2021) - Yu, Yue; Shuai, Ruixue; Liang, Lili; Qiu, Wenjuan; Shen, Linghua; Wu, Shengnan; Wei, Haiyan; Chen, Yongxing; Yang, Chiju; Xu, Peng; Chen, Xigui; Zou, Hui; et al.
Abstract: Background: To summarize the relationship between different MMUT gene mutations and the response to vitamin B12 in MMA. Methods: This was a retrospective study of patients diagnosed with mut‐type MMA. All patients with mut‐type MMA were tested for responsiveness to vitamin B12. Results: There were 81, 27, and 158 patients in the completely responsive, partially responsive, and nonresponsive groups, respectively, and the proportions of symptom occurrence were 30/81 (37.0%), 21/27 (77.8%), and 131/158 (82.9%), respectively ( p < .001). The median levels of posttreatment propionyl carnitine (C3), C3/acetyl carnitine (C2) ratio in the blood, and methylmalonic acid in the urine were all lower than pretreatment, and the median level of C3/C2 ratio in the completely responsive group was within the normal range. In 266 patients, 144 different mutations in the MMUT gene were identified. Patients with the mutations of c.1663G>A, c.2080C>T, c.1880A>G, c.1208G>A, etc. were completely responsive and with the mutations of c.1741C>T, c.1630_1631GG>TA, c.599T>C, etc. were partially responsive. The proportions of healthy/developmental delay outcomes in the three groups were 63.0%/23.5%, 33.3%/40.7%, and 13.3%/60.1%, respectively ( p < .001). Conclusion: Different mutations in the MMUT gene are associated with the effect of vitamin B12 treatment. Abstract : In the present study, we aimed to summarize the relationship between different MMUT gene mutations and the response to vitamin B12 in MMA. Our study indicated that different mutations in the MMUT gene are associated with the effect of vitamin B12 treatment.